2022
DOI: 10.1111/dmcn.15176
|View full text |Cite
|
Sign up to set email alerts
|

Peak functional ability and age at loss of ambulation in Duchenne muscular dystrophy

Abstract: AimTo correlate the North Star Ambulatory Assessment (NSAA) and timed rise from floor (TRF) recorded at age of expected peak with age at loss of ambulation (LOA) in Duchenne muscular dystrophy (DMD).MethodMale children with DMD enrolled in the UK North Start Network database were included according to the following criteria: follow‐up longer than 3 years, one NSAA record between 6 years and 7 years 6 months (baseline), at least one visit when older than 8 years. Data about corticosteroid treatment, LOA, genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…28,30,33 Moreover, other markers, namely timed function tests, already have been shown in the literature to predict loss of ambulation. [34][35][36][37] Future studies could expand on our findings to elucidate the predictive or therapeutic utility of these biomarkers for assessing motor functional changes in patients with DMD. Specifically, changes in these biomarkers could be assessed against muscle mass imaging markers (eg, lean body mass changes on dual-energy X-ray absorptiometry scan), as well as more granular motor function assessment scales (eg, the North Star Ambulatory Assessment), or compared with functional motor outcomes that have been demonstrated to predict loss of ambulation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…28,30,33 Moreover, other markers, namely timed function tests, already have been shown in the literature to predict loss of ambulation. [34][35][36][37] Future studies could expand on our findings to elucidate the predictive or therapeutic utility of these biomarkers for assessing motor functional changes in patients with DMD. Specifically, changes in these biomarkers could be assessed against muscle mass imaging markers (eg, lean body mass changes on dual-energy X-ray absorptiometry scan), as well as more granular motor function assessment scales (eg, the North Star Ambulatory Assessment), or compared with functional motor outcomes that have been demonstrated to predict loss of ambulation.…”
Section: Discussionmentioning
confidence: 91%
“…There is inherent variability in these biomarkers, depending on time of day, exercise, and dietary intake 28,30,33 . Moreover, other markers, namely timed function tests, already have been shown in the literature to predict loss of ambulation 34–37 . However, CK, serum Cr, and especially urine Cr, when assessed for trend in individuals, can give the clinician and researcher a fuller picture of the individual's status.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Zambon et al in their research that included 293 boys with DMD to determine the predictors for the age at loss of ambulation in those children; they concluded that timed rise from floor detected early in the disease course—which is one of the quantitatively assessed items in the GSGC scale—is one of the important predictors for loss of ambulation. 18…”
Section: Discussionmentioning
confidence: 99%
“…For ambulant boys, the clinical meaningfulness of NSAA as a measure of motor function has been demonstrated using longitudinal assessments 14,19–22 . The NSAA trajectories are characterized by awide range of expected inter‐ and intrasubject variability due to factors such as differing glucocorticoid regimens, natural variability with DMD genotype, and the subjectivity of the validated NSAA functional test, which can be effort‐dependent 14,20,21,23‐26 …”
Section: Introductionmentioning
confidence: 99%
“…Observed NSAA total scores overlaid onto simulated 95% confidence interval with median trajectory. Profiles stratified by baseline NSAA score ranges(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and colored by baseline age (orange, 4 years old; green, 5 years old; blue, 6 years old; and purple 7 years old). Colored arrows represent 1-year trajectory for each baseline age.…”
mentioning
confidence: 99%